Importance of the route of intravenous glucose delivery to hepatic glucose balance in the conscious dog. - Adkins, B A (1987)
To assess the importance of the route of glucose delivery in determining net hepatic glucose balance (NHGB) eight conscious overnight-fasted dogs were given glucose via the portal or a peripheral vein. NHGB was measured using the arteriovenous difference technique during a control and two 90-min glucose infusion periods. The sequence of infusions was randomized. Insulin and glucagon were held at constant basal levels using somatostatin and intraportal insulin and glucagon infusions during the control, portal, and peripheral glucose infusion periods (7 +/- 1, 7 +/- 1, 7 +/- 1 microU/ml; 100 +/- 3, 101 +/- 6, 101 +/- 3 pg/ml, respectively). In the three periods the hepatic blood flow, glucose infusion rate, arterial glucose level, hepatic glucose load, arterial-portal glucose difference and NHGB were 37 +/- 1, 34 +/- 1, 32 +/- 3 ml/kg per min; 0 +/- 0, 4.51 +/- 0.57, 4.23 +/- 0.34 mg/kg per min; 101 +/- 5, 200 +/- 15, 217 +/- 13 mg/dl; 28.5 +/- 3.5, 57.2 +/- 6.7, 54.0 +/- 6.4 mg/kg per min; +2 +/- 1, -22 +/- 3, +4 +/- 1 mg/dl; and 2.22 +/- 0.28, -1.41 +/- 0.31, and 0.08 +/- 0.23 mg/kg per min, respectively. Thus when glucose was delivered via a peripheral vein the liver did not take up glucose but when a similar glucose load was delivered intraportally the liver took up 32% (P less than 0.01) of it. In conclusion portal glucose delivery provides a signal important for the normal hepatic-peripheral distribution of a glucose load.